2022
DOI: 10.6004/jnccn.2022.0015
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Lymphomas, Version 2.2022, NCCN Clinical Practice Guidelines in Oncology

Abstract: Peripheral T-cell lymphomas (PTCLs) are a heterogeneous group of lymphoproliferative disorders arising from mature T cells, accounting for about 10% of non-Hodgkin lymphomas. PTCL-not otherwise specified is the most common subtype, followed by angioimmunoblastic T-cell lymphoma, anaplastic large cell lymphoma, anaplastic lymphoma kinase–positive, anaplastic large cell lymphoma, anaplastic lymphoma kinase–negative, and enteropathy-associated T-cell lymphoma. This discussion section focuses on the diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 129 publications
2
43
2
5
Order By: Relevance
“…In contrast with previous studies, 10,18 Aspa-based regimens are preferred according to guidelines. 16,22 In our study, although Aspa-based regimens did not display significant superiority in multivariate analysis, univariate analysis already showed that Aspa-based regimens significantly improved PFS1 and partly improved OS compared to non-Aspa-based ones. The lack of statistical significance may be attributed to the confounding factors, particularly the concomitant application of Aspa and other agents, and the prominent hematological toxicity of the SMILE regimen [23][24][25] which often led to suboptimal dosage in clinical practice.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In contrast with previous studies, 10,18 Aspa-based regimens are preferred according to guidelines. 16,22 In our study, although Aspa-based regimens did not display significant superiority in multivariate analysis, univariate analysis already showed that Aspa-based regimens significantly improved PFS1 and partly improved OS compared to non-Aspa-based ones. The lack of statistical significance may be attributed to the confounding factors, particularly the concomitant application of Aspa and other agents, and the prominent hematological toxicity of the SMILE regimen [23][24][25] which often led to suboptimal dosage in clinical practice.…”
Section: Discussioncontrasting
confidence: 49%
“…However, for advanced‐stage patients, current treatment modalities especially comprehensive therapy still have certain shortcomings, with a 5‐year OS <20% according to most previous literature reports 11‐15 . The National Comprehensive Cancer Network (NCCN) guideline recommend multidisciplinary therapy for advanced‐stage ENKTL, including asparaginase (Aspa)‐based CT, RT and hematopoietic stem cell transplantation (HSCT) consolidation as appropriate; clinical trials are preferred as there is no established consensus on the optimal treatment 16 . Previous studies mostly focused on early‐stage disease, while few large‐sample researches specifically investigated newly diagnosed advanced‐stage ENKTLs yet.…”
Section: Introductionmentioning
confidence: 99%
“…After the initial stage assessment, all patients were given 6–8 cycles of first-line chemotherapy regimens with or without radiotherapy according to the latest NCCN guidelines, and patient tolerance and comorbidities. 6 , 30 Serial ctDNA profiling was conducted during the patient’s therapy course. The Eastern Cooperative Oncology Group (ECOG) performance status was also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, long-term outcomes have been highly unsatisfactory for AITL patients treated with anthracycline-based regimens as reported by different groups, with 5-year PFS estimates of 18%, 13%, and 20% according to the ITCLP , British Columbia Cancer Agency (BCCA) group, and Swedish National Lymphoma Registry , respectively ( 10 , 115 , 116 ). This has led to several guidelines, including that of the National Comprehensive Cancer Network (NCCN), to recommend enlisting patients with AITL in clinical trials as preferred primary therapeutic strategy ( 117 ).…”
Section: Treatmentmentioning
confidence: 99%